2012
DOI: 10.3341/jkos.2012.53.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Screening for Diabetic Retinopathy in Diabetic Patients Aged ≥ 40 Years Using the KNHANES IV

Abstract: 1.08-1.89), 건강하다고 생각하는 군(OR=1.5, 95% CI:1.14-2.09)들로 분석되었다. The term 'spouse' refers to an individual who is legally married or cohabiting, 'without spouse' refers to an individual who is single, divorced, or separated; ‡ Lifetime smoker included respondents who reported that they have smoked at least 100 cigarettes in their lifetime and now smoke; § Moderate-intensity activities as that lasting 10 minutes or more and increasing heart rate slightly compared with sedentary lifestyle. Subjects were asked the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 17 publications
6
10
1
Order By: Relevance
“…Meanwhile, Lim and Choi ( 2 ) analyzed Korea National Health and Nutrition Examination Survey IV results and stated that 464 of 1,257 patients underwent ophthalmological examination for diabetic retinopathy within a year, accounting for only 36.9% of patients. Therefore, the probability of opportunistic examination by ophthalmologists was presumed to be 36.9%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Lim and Choi ( 2 ) analyzed Korea National Health and Nutrition Examination Survey IV results and stated that 464 of 1,257 patients underwent ophthalmological examination for diabetic retinopathy within a year, accounting for only 36.9% of patients. Therefore, the probability of opportunistic examination by ophthalmologists was presumed to be 36.9%.…”
Section: Methodsmentioning
confidence: 99%
“…In Korea, according to Lim and Choi ( 2 ), 36.9% of patients with diabetes aged > 40 yr underwent screening for diabetic retinopathy in the Korea National Health and Nutrition Examination Survey IV. This proportion was markedly lower than that in advanced countries, including 51% in the USA and 59% in the UK ( 3 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age showed inconsistent results, including no significant association with adherence rates [16], lower nonadherence rates for those aged 65 years or older [18], and higher nonadherence rates for those aged 80 years or older [15]. Additionally, gender also showed inconsistent association across studies of people with DM in Korea, including higher adherence rates in women [16], or no significant difference between men and women [15,18], while it was not a significant factor in foreign countries [8,13,14,17]. Several community-based studies of the general population have reported that the prevalence of visual impairment and blindness [19] and the use of eye examinations [20] were higher in women, as was the fundus examination rate for people with diabetic retinopathy [21].…”
Section: Introductionmentioning
confidence: 95%
“…Studies have shown that better knowledge or education about DM [8,14], in addition to sociodemographic characteristics such as older age, longer DM duration, and insurance coverage [8,17], is associated with adherence to AEEs in foreign countries. In Korea, an education level of college graduates or above and a DM duration of 5 years were found to have a positive association with AEEs, but insurance coverage was not a significant factor because of the provision of national health insurance [16,18]. Age showed inconsistent results, including no significant association with adherence rates [16], lower nonadherence rates for those aged 65 years or older [18], and higher nonadherence rates for those aged 80 years or older [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation